Mapping geographical inequalities in oral rehydration therapy coverage in low-income and middle-income countries, 2000–17 - Local Burden of Disease Diarrhoea Collaborators (Elsevier, 2022)
This article was published in The Lancet Global Health by Elsevier [© 2020 The Author(s). Published by Elsevier Ltd. This is an Open Access article under the CC BY 4.0 license.] and the definite version is available at: https://doi.org/10.1016/S2214-109X(20)30230-8 The Journal's website is at: https://reader.elsevier.com/reader/sd/pii/S2214109X20302308?token=3AE802BA5AFFD7D5E5FF7ACD9823D127717DFB17CA451456356DF3A3FE5E5F7FD692DD83CA6668D54EEBF069BB6ACE3C&originRegion=eu-west-1&originCreation=20220525060713